A New Approach for Query Processing and Optimization Base on the Fuzzy Object Algebra and Equivalent Transformation Rules. (2017) - T.Nguyen, Thuan; V.Doan, Ban; N.Truong, Chau; T.T.Tran, Trinh
No abstract available